2017
DOI: 10.1111/his.13239
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping of mammary‐like adenocarcinoma of the vulva shows molecular similarity to breast carcinomas

Abstract: Breast cancer subtyping can be applied to vulvar MLAs. All four intrinsic molecular subtypes are seen, with frequencies similar to those in breast carcinoma. Our results support the potential use of breast cancer molecular profiling algorithms to guide treatment for these cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…A recent IHC study showed that MLAV can be classified into four breast intrinsic subtypes, including a HER2 + /ER − group ( Tran et al 2015 ; Tessier-Cloutier et al 2017 ). Here we note that during the initial pathology workup for the vulvar biopsy for this cancer, the diagnosis of MLAV was not favored on the basis of ER, mammaglobin, and GCDFP-15 negativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent IHC study showed that MLAV can be classified into four breast intrinsic subtypes, including a HER2 + /ER − group ( Tran et al 2015 ; Tessier-Cloutier et al 2017 ). Here we note that during the initial pathology workup for the vulvar biopsy for this cancer, the diagnosis of MLAV was not favored on the basis of ER, mammaglobin, and GCDFP-15 negativity.…”
Section: Discussionmentioning
confidence: 99%
“…Current understanding suggests they are modified vulvar eccrine glands that can give rise to a variety of tumors including vulvar adenocarcinomas ( van der Putte 1994 ). Treatment guidelines are traditionally the same across vulvar carcinomas, but new evidence suggests the transposition of some of the preexisting diagnostic and treatment approaches for breast carcinomas to mammary-like adenocarcinomas of the vulva ( McMaster et al 2013 ); these include sentinel node biopsy and molecular subtyping combined with adjuvant therapy ( Abbott and Ahmed 2006 ; Perrone et al 2009 ; Kazakov et al 2011 ; Butler et al 2014 ; Tessier-Cloutier et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Extramammary Paget's disease (EMPD) is a rare intraepithelial adenocarcinoma that principally affects the genital and axillary regions. Although the pathogenesis remains to be clarified, it has been reported to resemble breast cancer (BC) in immunohistochemical and molecular profiles . As EMPD typically grows slowly and is diagnosed in situ, the prognosis after surgical resection is generally favorable.…”
Section: Introductionmentioning
confidence: 99%
“…The in situ VPD cases were more frequently categorized as luminal A (70%) compared with 29% invasive VPD. HER2/neu was overexpressed in 41% of cases, more commonly in the invasive ones (43% vs 30%) 56. We can conclude, after almost 30 years of fragmented and heterogeneous results, that HER2/neu overexpression characterizes at least one-third of VPD lesions, probably a subgroup with worse prognosis related to invasion, recurrence, and node metastases.…”
Section: Resultsmentioning
confidence: 73%